PENGARUH MODEL PEMBELAJARAN DAN KEMAMPUAN AWAL TERHADAP HASIL BELAJAR PESERTA DIDIK DALAM MATERI KIMIA KELAS XI IPA SMAN 4 MAKASSAR - Fandi Ahmad (Chemistry Education Review (CER), 2017)
The study aimed at examining (1) the difference between learning outcomes of grade XI IPA students at SMAN 4 Makassar taught by using Think-Pair-Share (TPS) learning model and the ones using direct learning on Hydrolisis of Salt, (2) the diffrence between learning outcomes of grade XI IPA students at SMAN 4 Makassar with high initial ability on Hydrolysis of Salt, (3) the interaction betwen learning model and initial ability in influenching learning outcomes of grade XI IPA students at SMAN 4 Makassar on hydrolysis of Salt. The Study was a quasi-experiment research which employed factorial 2x2 design.The population of the study was all grade XI IPA students at SMAN 4 Makassar of academic year 2012/2013 with 7 classes. The samples were two classes, namely grade XI IPA1 and grade XI IPA3 selected using random sampling technique. Hypothesis test was conducted by employing two-way analysis of variant of GLM univariat supported by SPSS 16.0 program. The results of the study revealed that (1) therewas a difference between learning outcomes of grade XI IPA students at SMAN 4 Makassar taught by using TPS learning model and the ones using direct learning on Hydrolysis of salt, (2) there was a difference between learning outcomes of grade XI IPA students at SMAN 4 Makassar with high initial ability and low initial ability on Hydrolysis of Salt, (3) there was interaction between learning model and initial ability in influenching learning outcomes of grade XI IPA students at SMAN 4 Makassar on Hydrolysis of Salt. The average of students’ learning outcomes taught by using TPS learning model was higher than taught by using direct learning model, and learning outcomes of students who have high initial ability was higher than students with low initial ability.